Online Communication in Language Learning and Teaching - Lamy, M. author. aut Link
XVI, 260 p.
Keywords: This offers a framework for thinking about technologies that allow online communication, for example, forums, chats, real-time platforms as well as virtual worlds and mobile devices, and the practical issues of using them. The authors offer a thorough appraisal of the potential benefits and challenges of learning and teaching a language online.